2008
DOI: 10.1021/bp070294t
|View full text |Cite
|
Sign up to set email alerts
|

Expression System for Synthesis and Purification of Recombinant Human Growth Hormone in Pichia pastoris and Structural Analysis by MALDI-ToF Mass Spectrometry

Abstract: An expression system in Pichia pastoris for the production and purification of recombinant human growth hormone (rHGH) was designed and implemented. hGH cDNA sequence was cloned into pPICZRA vector under the control of AOX1 promoter, which included a polyhistidinetag on the amino terminal end to enable affinity purification and a target site for Factor Xa protease such that protease cleavage in vitro would produce rhGH without any non-native Nand C-termini. Analyses of the affinity-purified rhGH product by mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 14 publications
0
8
1
Order By: Relevance
“…Basidiomycete mushrooms have not been considered as a platform for the production of therapeutic proteins until now [20]. Previously, several other expression system such as Bacillus subtilis [21], Escherichia coli [22], Pichia pastoris [23], transgenic mice [24], and transgenic goat [25] have been used for producing hGH. This is the first report to express hGH in P. eryngii by the Agrobacterium-mediated transformation system, and we have demonstrated that it was feasible to express a pharmaceutically important gene in mushroom.…”
Section: Discussionmentioning
confidence: 99%
“…Basidiomycete mushrooms have not been considered as a platform for the production of therapeutic proteins until now [20]. Previously, several other expression system such as Bacillus subtilis [21], Escherichia coli [22], Pichia pastoris [23], transgenic mice [24], and transgenic goat [25] have been used for producing hGH. This is the first report to express hGH in P. eryngii by the Agrobacterium-mediated transformation system, and we have demonstrated that it was feasible to express a pharmaceutically important gene in mushroom.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that the proteolysis was associated with the cargo protein FKBP12 because the Factor Xa sequence has not been proteolyzed by P. pastoris in other published reports [36, 37]. Therefore, two new constructs were designed, which were pJV3 (MBP-FXa-Spe9-myc-His6) and pJV4 (MBP-FXa-EGFP-myc-His6), as illustrated in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Normally, the Factor Xa site is used after purification to separate the cargo protein from MBP. This protease recognition site (Ile-Glu-Gly-Arg) should not be recognized in P. pastoris [36, 37]. Because of our initial findings, we hypothesized that the Factor Xa site was being recognized by an uncharacterized protease inside the P. pastoris cell and, as a result, the Factor Xa site was replaced with an enterokinase cleavage site.…”
Section: Discussionmentioning
confidence: 99%
“…Production and purification of recombinant BJ46a rBJ46a protein was produced according to the manufacturer's instructions [10,14]. Briefly, recombinant GS115-BJ46a was amplified to an OD 600 of 4.0 in log-phase growth in 25 ml of BMGY medium [1% (w/v) yeast extract, 2% (w/v) peptone, 1.34% (w/v) yeast nitrogen base, 0.1 mol/l potassium phosphate buffer pH 6.0, 4 Â 10 -5 % (w/v) biotin, 1% (v/v) glycerol, 4 Â 10 -3 % (w/v) histidine] at 301C using a shaking incubator (300 rpm).…”
Section: Methodsmentioning
confidence: 99%